(Mis)Reading Muslims and Multiculturalism - Kivisto, Peter (Social Inclusion, 2013)
This paper offers a review and conceptual reflection on fears about the Muslim pres ence and lack of inclusion into Western European societies and the core features of criticisms of multiculturalism. It does so by first addressing the misreadings of Islam and multiculturalism in influential works by Christopher Caldwell and Paul Scheffer. It then addresses the main points of their critiques by examining the role of the state in Muslim incorporation, framing multicultur alism theoretically in terms of claims-making, and offering evidence of the ways in which Muslim claims-making has occurred.